(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The main target of this study was to assess the Critical Analysis of Bibliography in Scholarly Papers: The Review of the Components and the Management Tools for Academic Libraries in Akwa Ibom State Tertiary Institution. Descriptive survey design was adopted for the study. The study was conducted in Akwa Ibom Sate. The target population for the study was all librarians in Akwa Ibom State. Stratified sampling technique was used to select 25 Librarians from University of Uyo, 17 from Akwa Ibom State University, 5 from College of Education and 10 from Polytechnic. This gave a total of 57 respondents used in the study. The research instruments used for data collection was a structured questionnaire title “BIBLIOGRAPHY COMPONENTS AND MANAGEMENT TOOLS QUESTIONNAIRE (BCMTQ)”. Face and content validation of the instrument was carried out by an expert in testing, measurement, and evaluation to ensure that the instrument has the accuracy, appropriateness, and completeness for the study under consideration. The reliability coefficient obtained was 0.80, and this was high enough to justify the use of the instrument. The test for significance was done at 0.05 alpha levels. The study discovered that bibliography is to help library users in locating items of information for study and research. A bibliography also acts as a key to the large mass of information that exists today. The study concluded bibliography involves the listing of articles, books, journals used in building up the literature of a given study. It also entails the listing of books in an organized manner. Bibliographies are very vital in writing research work. They provide the author(s) the opportunity to direct the readers towards the source of information and references used and made respectively while writing their reports. One of the recommendations made in the study was that bibliography should be introduced to both old and modern libraries to provide quick and easy access to information contained in documents.